Targeting TRIM Proteins: A Quest towards Drugging an Emerging Protein Class. (18th March 2021) - D'Amico, Francesca; Mukhopadhyay, Rishov; Ovaa, Huib; Mulder, Monique P. C.
Abstract: The ubiquitylation machinery regulates several fundamental biological processes from protein homeostasis to a wide variety of cellular signaling pathways. As a consequence, its dysregulation is linked to diseases including cancer, neurodegeneration, and autoimmunity. With this review, we aim to highlight the therapeutic potential of targeting E3 ligases, with a special focus on an emerging class of RING ligases, named tri‐partite motif (TRIM) proteins, whose role as targets for drug development is currently gaining pharmaceutical attention. TRIM proteins exert their catalytic activity as scaffolds involved in many protein–protein interactions, whose multidomains and adapter‐like nature make their druggability very challenging. Herein, we give an overview of the current understanding of this class of single polypeptide RING E3 ligases and discuss potential targeting options. Abstract : It can be hard to get TRIM : TRIM proteins, the largest subfamily of single polypeptide RING E3 ligases, are currently gaining attention as targets for drug development. However, developing effective targeting options for TRIMs is challenged by their multidomain scaffolding nature correlating with multifunctional biological roles. Herein, we highlight our current understanding of TRIMs and discuss potential targeting options.